A new species of Atelopus (Anura: Bufonidae) from southern Peru - Herrera-Alva, Valia; Díaz, Vladimir; Castillo, Ernesto; Rodolfo, César; Catenazzi, Alessandro (Zootaxa, 2020)
We describe a new harlequin frog (genus Atelopus) from the cloud forest near Anchihuay (Anco District, Ayacucho Department) from 2000 to 2150 m elevation in southern Peru, representing the first record for the genus in the Department of Ayacucho. The new species has a maximum snout-vent length of 21.5 mm in females and 21.6 mm in males, and resembles A. erythropus in general appearance, small size, and dorsal coloration. The new species can be distinguished from A. erythropus by its unique pattern of ventral coloration, dorsal skin texture, and snout shape. We detected the presence of the pathogenic fungus Batrachochytrium dendrobatidis in individuals of the new species. This pathogen is threatening the survival of harlequin frogs throughout the Neotropics. In addition to chytridiomycosis, habitat loss further threatens the single locality where the new species is known to occur.